Representasi Perempuan dalam Film Ayat-Ayat Cinta - Rosnandar Romli; Mella M. Roosdinar; Aat Ruchiat Nugraha (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2018)
Film as part of mass communication has a considerable influence on the formation of opinions that occur in society. One of the best-selling films in 2008 was the film Ayat-Ayat Cinta. This research was carried out with assumptions about the existence of ideological battles that took place in a media discourse and representation of women in a film. The purpose of this research was to find out the representation of women in the film Ayat-Ayat Cinta through events in film stories that were commodified by cinematographers and audiences. The type of research method used is qualitative descriptive research analyzing media content with critical discourse analysis methods by Sara Mills. The research was conducted by dissecting the text in the film, looking at the subject-object position and the producer-reader position in climax scenes, to see how women are represented in the scenes. The results showed that the film still uses male perspectives in viewing the events; women are still represented more as objects than subjects; women are still viewed from the perspective of other parties (mostly men); the film leads the audience to identify themselves with male figures; and this film still affirms the patriarchal ideology